The impact of information technology applications on the quality of life of disabled older adults in nursing homes in China: a qualitative study - Zhang, Hong; Liao, Xiaoyan; Liang, Shuang; Tong, Lifang; Shen, Jun; Peng, Bin; Wu, Lin; Gao, Lu; Jia, Qianying; Ren, Liu; Luo, Lanyue; Wang, Yixin; et al. (Frontiers in Public Health, 2025)
ObjectiveChina’s smart aging policy system has been evolving to become more comprehensive, continuously promoting the application of information technology in nursing homes. This study explores the adaptation process and experiences of disabled older adults with the use of information technology in nursing homes from four perspectives: physiological, psychological, social, and environmental, and examines its impact on their quality of life.MethodsAn interpretative phenomenological approach was adopted, with purposive sampling used to recruit participants. Semi-structured interviews were conducted with 14 disabled older adults, and the data were analyzed using Van Manen’s phenomenology of practice method.ResultsFour main themes and 16 sub-themes were identified: Physical Health and Functional Capacity: subjective health perception, physical functioning, chronic disease management, sleep quality, and nutritional status; Psychological Wellbeing and Emotional Support: attitudes toward aging, negative emotions, emotional companionship, and sense of meaning in life; Social Relationships and Social Engagement: interactions with family and friends, participation in social activities, social roles, and social support; and Environmental Adaptation and Digital Challenges: safety and comfort of the living environment, ease of independent mobility, the ‘digital divide’, and protection of personal privacy and data.ConclusionThe application of information technology in nursing homes in China has partially resolved longstanding issues in traditional older adults care, such as inaccurate health management, lack of personalized and diverse services, and inefficient resource allocation. These advancements have contributed to improving the quality of life for older adults in nursing homes. However, new challenges have emerged, including the ‘digital divide,’ data misuse, and privacy breaches. To fully leverage the benefits of information technology, it is crucial to enhance the digital literacy of disabled older adults, provide robust technical support during implementation, and prioritize data security and privacy protection. These measures will help maximize the positive effects of information technology on the quality of life of disabled older adults.